Brain functional connectivity alterations associated with neuropsychological performance 6–9 months following SARS‐CoV‐2 infection. Issue 4 (2nd December 2022) - Voruz, Philippe; Cionca, Alexandre; Jacot de Alcântara, Isabele; Nuber‐Champier, Anthony; Allali, Gilles; Benzakour, Lamyae; Lalive, Patrice H.; Lövblad, Karl O.; Braillard, Olivia; Nehme, Mayssam; Coen, Matteo; Serratrice, Jacques; et al.
Abstract: Neuropsychological deficits and brain damage following SARS‐CoV‐2 infection are not well understood. Then, 116 patients, with either severe, moderate, or mild disease in the acute phase underwent neuropsychological and olfactory tests, as well as completed psychiatric and respiratory questionnaires at 223 ± 42 days postinfection. Additionally, a subgroup of 50 patients underwent functional magnetic resonance imaging. Patients in the severe group displayed poorer verbal episodic memory performances, and moderate patients had reduced mental flexibility. Neuroimaging revealed patterns of hypofunctional and hyperfunctional connectivities in severe patients, while only hyperconnectivity patterns were observed for moderate. The default mode, somatosensory, dorsal attention, subcortical, and cerebellar networks were implicated. Partial least squares correlations analysis confirmed specific association between memory, executive functions performances and brain functional connectivity. The severity of the infection in the acute phase is a predictor of neuropsychological performance 6–9 months following SARS‐CoV‐2 infection. SARS‐CoV‐2 infection causes long‐term memory and executive dysfunctions, related to large‐scale functional brain connectivity alterations. Abstract : One hundred and ten patients, with either severe, moderate, or mild disease in the acute phase underwent neuropsychological and olfactory tests, as well as completed psychiatric and respiratory questionnaires at 223 ± 42 days postinfection. Additionally, a subgroup of 50 patients underwent functional magnetic resonance imaging. The severity of the infection in the acute phase is a predictor of neuropsychological performance 6–9 months following SARS‐CoV‐2 infection. SARS‐CoV‐2 infection causes long‐term memory and executive dysfunctions, related to large‐scale functional brain connectivity alterations.